Anthropology of the brain consciousness, culture, and free will - Bartra, Roger (Cambridge University Press, 2014)
"Anthropology of the Brain In this unique exploration of the mysteries of the human brain, Roger Bartra shows that consciousness is a phenomenon that occurs not only in the mind but also in an external network, a symbolic system. He argues that the symbolic systems created by humans in art, language, in cooking or in dress, are the key to understanding human consciousness"-- Provided by publisher.